Gerakan 1000 Masker Melawan Corona: Pembagian di Kecamatan Denpasar Utara - Ni Wayan Ardiarani Utami; Kadek Risna Puspita Giri (Jurnal Lentera Widya, 2020)
The Coronavirus epidemic (Covid-19) which has infected the entire world has also arrived in Indonesia. Bali Province was not spared from this virus attack. Covid-19 Positive Cases in Denpasar City accounted for 31% of all positive cases in Bali Province. One of the recovered patients came from North Denpasar District, Peguyangan Kangin Village. The Central Government through the Ministry of Health of the Republic of Indonesia has issued a Circular Letter of the Minister of Health Republic of Indonesia concerning the Protocol to Prevent the Transmission of the Covid-19 virus, one of which is by using masks for people who leave their homes. This has caused STD Bali as a Design School to participate in preventing the transmission of the Covid-19 virus. STD Bali in Community Service activities carried out the "Movement of 1000 masks" to prevent the transmission of the Covid-19 virus. The method used is to form a Production Team, Design Team, Distribution Team and Documentation Team. The Production Team is responsible for the supply, distribution and manufacture of masks. The Design Team is in charge as infographic planning, design, packaging and printing. The Distribution Team did the mapping, data collection and distribution of masks and the Documentation Team was tasked with documenting each activity. Implementation of the 1000 Masks Movement Activity, one of which was distributed in Banjar Ambengan Peguyangan Kangin, North Denpasar. Banjar Ambengan consists of 400 residents, of which the heterogeneous population background is due to migrants from outside Banjar who have become residents of the Banjar Dinas Ambengan. The submission of masks in Banjar Ambengan was carried out by the Distribution and Documentation Team and was received by Kelian Adat and the Head of the Banjar Ambengan Hamlet, where in this activity the health protocol was implemented by maintaining a minimum distance of 1 m and using masks. Submission of the mask as well as an explanation of the packaging that contains info about the Covid-19 virus, how to prevent and how to use the mask correctly. It is hoped that this activity can help the community in preventing the transmission of the Covid-19 virus and correct information about how to prevent the transmission of the Covid-19 virus.